PENGARUH LATIHAN KEKUATAN OTOT LENGAN TERHADAP KEMAMPUAN CHEST PASS DALAM PERMAINAN BOLA BASKET - Trinanda, Aditya; Dwi Septian, Mahayudi; Serka Yudha Pratama, Octavian; Armanjaya, Satria; Triyanto, Triyanto (Jurnal Arena Olahraga Silampari, 2023)
The purpose of this research is to determine the effect of arm muscle strength training on chest pass ability in basketball games among basketball extracurricular students at SMA Negeri 19 Palembang. The method used in this research is an experiment in the form of a One-Group Experimental, with a pre-test (before being given treatment) and post-test (after being given treatment) The population in this study were all extracurricular basketball students at SMA Negeri 19 Palembang and the sampling technique was total sampling. The data collection technique is tests and measurements and the data collection tool used is measuring the results of the chest pass using the wall throw test. The data analysis technique in this research is the Paired Sample Test (t-test). Based on the results of hypothesis testing using t-test statistics, it was obtained that t = 20.91 and the table was 1.70. Thus the thing table, or 20,911.70, this result states that there is an influence of arm muscle strength training on chest pass ability in extracurricular basketball students' basketball games. Keywords: Arm Muscle Strength Training, Chest Pass,Basket